PENERAPAN MODEL PEMBELAJARAN ACTIVE LEARNING PADA MATA PELAJARAN IPAS MATERI MEMENUHI KEBUTUHAN HIDUPKU UNTUK MENINGKATKAN AKTIVITAS BELAJAR SISWA - Astina, Dewi; Munirah, Munirah; Bakari, Aljunaid (DIRASATUL IBTIDAIYAH, 2024)
AbstractThis research aims to increase the learning activities of class IV students at SDN 81 Sipatana, Gorontalo City through the use of the Active Learning learning model in 2024. This research method uses the type of classroom action research (PTK). The subjects in this research were class IV students at SDN 81 Sipatana, Gorontalo City, the number of students for the 2023-2024 academic year was 21 students consisting of 9 girls and 12 boys. This research was conducted in 2 cycles. Each cycle consists of 2 meetings and 4 stages which refer to the Kemmis and Taggart model, namely: planning, action, observation and reflection. The results of this research show that implementing the Active Learning learning model can increase students' learning activities in learning science and science material to meet their living needs for class IV SDN 81 Sipatana, Gorontalo City. Data analysis in the research used descriptive percentage formulas for teacher activities and student activities. This can be seen from the increase in each cycle, namely in cycle I getting teacher activity 73.3%, student activity getting 66.6%, and increasing again in cycle II getting teacher activity 83.3%, and student activity getting 80.9% . So it can be concluded that implementing Active Learning can increase students' learning activities in science and science learning material to meet the life needs of class IV SDN 81 Sipatana, Gorontalo City.Keywords: Active Learning, Learning Activities, Materials to Meet My Life Needs  AbstrakPenelitian ini bertujuan untuk meningkatkan aktivitas belajar siswa kelas IV SDN 81 Sipatana Kota Gorontalo melalui penggunaan model pembelajaran Active Learning tahun 2024. Metode penelitian ini menggunakan jenis penelitian tindakan kelas (PTK). Subjek dalam penelitian ini adalah siswa kelas IV SDN 81 Sipatana Kota Gorontalo, jumlah siswa tahun ajaran 2023-2024 sebanyak 21 siswa yang terdiri dari perempuan 9 dan 12 laki-laki. Penelitian ini dilakukan dalam 2 siklus. Setiap siklus terdiri dari 2 pertemuan dan 4 tahap yang mengacu pada model Kemmis and Taggart yaitu: perencanaan, tindakan, observasi dan refleksi. Hasil penelitian ini menunjukkan bahwa mengimplementasikan model pembelajaran Active Learning dapat meningkatkan aktivitas belajar siswa pada pembelajaran IPAS materi memenuhi kebutuhan hidupku kelas IV SDN 81 Sipatana Kota Gorontalo. Analisis data pada penelitian menggunakan rumus deskrptif presentase untuk aktivitas guru, dan aktivitas siswa. Hal ini dapat dilihat dari peningkatan tiap siklus yakni pada siklus I memperoleh aktivitas guru 73,3%, aktivitas siswa memperoleh  66,6%, dan meningkat lagi pada siklus II memperoleh aktivitas guru 83,3%, dan aktivitas Siswa memperoleh 80,9%. Maka dapat disimpulkan bahwa mengimplementasikan pembelajaran Active Learning dapat meningkatkan Aktivitas belajar siswa pada pembelajaran IPAS materi memenuhi kebutuhan hidupku kelas IV SDN 81 Sipatana Kota Gorontalo. Kata Kunci: Active Learning, Aktivitas Belajar, Materi Memenuhi Kebutuhan Hidupku.